APPLICATION OF PASSIVE REMOTE SENSING TO INVESTIGATE TRANSMISSIVITIES OF TREES CANOPIES USING GROUND-BASED UPWARD-LOOKING MICROWAVE RADIOMETERS - Chung, Doan Minh; Kostov, Kosta; Anh, Vo Thi Lan; Quang, Huynh Xuan; Anh, Tran Tuan; Nguyen, Mai Thi Hong; Ngoc, Le Dai (Vietnam Journal of Science and Technology, 2017)
Abstract. In Vietnam, in recent years, remote sensing technology has developed very strongly in many different application areas. Besides, remote sensing using optical satellite, radar satellites, passive remote sensing includingmicrowave radiometers has been studied for a long time. This paper presents the results of the study on emission and transmissivity of trees canopyusing ground-based upward-looking microwave radiometers at two bands, L and X which were manufactured and calibrated byour research group at the Space Technology Institute - Vietnam Academy of Science and Technology. In the field measurement campaigns in 2015 and 2016, brightness temperatures were calculated from the output signal of the radiometers that measure trees canopy, transmissivity of the canopy in L-band, and X-band was calculated from the physical temperature of the canopy,the brightness temperature of blue sky and the brightness temperature of the canopy after the radiometers were calibrated using blue sky and the black body at the corresponding frequency base on transmissivity model. These results provide empirical evidence to quantify the characteristics of microwave which is transmitted in the canopy to support the analysis and assessment of corresponding data obtained when the device is set high above and measuring downwards to the canopy.